Webd Control in Pinus Plantations II - Effect of Weedicides on the Growth of Lantana camara - Soni, Prafulla (Indian Forester, 1980)
Present study is a preliminary investigation on the control of Laniana camara in Pinus plantations. The study was carried on in a two year old Pinus kesiya plantation located in Forest Research Institute, Dehar Dun. From the results obtained it has been concluded that only one application of Brush killer to Lantana shoots has reduced the density of Lantana by 76% and it is presumed that subsequent spraying for 2-3 years may eliminate the word completely from this area.